New Clinical Trials Regulations-2013 in India & its Possible Impact on Indian Clinical Trials Framework - K, Shantanu; P, Bhagwat (Indian Journal of Pharmacy Practice)
Indian regulators recently enforced two new clinical trials regulations namely “122 DAB- Compensation in case of injury or death during clinical trial” [Drugs & Cosmetics (First Amendment) Rules, 2013] & “122 DAC, (1) Permission to conduct Clinical Trial” [Drugs & Cosmetics (Second Amendment) Rules, 2013] that promise to reform Clinical-Trials conducted in India. Clinical trial sponsors are now liable for injuries or deaths that occur during the course of a clinical trial, and will be required to compensate subjects or the subject's family. The compensation mechanism does appear to be very comprehensive and is very strongly in favor of the volunteer who participate in the trials. The regulations insist on medical management to be provided to the volunteer for as long as required and also indicate that financial compensation should be paid to the volunteers or their nominee. The regulations also define cases which would be termed as clinical trials related injury/death. Product inefficacy has been termed as a clinical trial injury. This paper views the recent amendments as a whole, & provides a rationale for change, and offers an interrelated set of recommendations to improve the protection of human participants and enable the amendment to operate more efficiently.
Keywords: CDSCO; Clinical trial regulations; DCGI; ethical committee; ICMR